EFFECTIVENESS OF MODELS OF HEAVY METALS CONTENT'S DISTRIBUTION IN SURFACE WATER (ON THE EXAMPLE OF THE POLTAVA REGION) - Жуков, М.; Клипа, А.; Стахів, І. (Київський національний університет імені Тараса Шевченка, 2012)
A comparative assessment of the effectiveness of four models (normal, lognormal, compositional normal and compositional lognormal) of heavy metals content's distribution in surface waters at artificially reduced samples has been conducted. The estimations of areas of the territory in which the level of heavy metals exceeds the specified critical limits were made and then direct estimates that were obtained during the calculation of the total volume of data were compared with previous data. Both composite models were found most effective, and the accuracy assessments areas obtained by the reduced samples were equal direct estimates.

Проведено порівняльну оцінку ефективності чотирьох моделей розподілу (нормальної, логнормальної, композиційнонормальної та композиційно-логнормальної) вмісту важких металів у поверхневих водах на штучно скорочених вибірках. Виконано оцінки площ території, на яких рівень важких металів перевищує задані критичні границі та порівняно їх з прямими оцінками, які були отримані під час розрахунку повного об'єму даних. Встановлено, що обидві композиційні моделі є найбільш ефективними, причому за точністю оцінки площ, одержані по зменшеним вибіркам, майже не поступаються прямим оцінкам.
ОЦІНКА ЕФЕКТИВНОСТІ МОДЕЛЕЙ РОЗПОДІЛУ ВМІСТУ ВАЖКИХ МЕТАЛІВ У ПОВЕРХНЕВИХ ВОДАХ (НА ПРИКЛАДІ ПОЛТАВСЬКОЇ ОБЛАСТІ)